Renoir, susceptibilités épidermiques - Dubreuil, Nicole (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 1999)
Taking as its point of departure Renoir’s lifelong fascination with the representation of skin, this article explores how this motif, relinquished by many “pleinairistes” because of its incestuous links with traditional painting, expresses the very core of Renoir’s professional and personal idiosyncrasies and sustains his ambiguous position within modernism. Renoir’s foreword to a 1911 French re-edition of Cennino Cennini’s Libro del Arte sheds light on the anxieties which seemed to plague a decorator turned easel painter, and were incited by his avant-garde posture to shun academic training. Not only is the representation of skin related for Renoir to never-ending technical queries and problems; the fantasmatic conception of the female body in which it takes part, especially during the artist’s old age, reveals deeper fears connecting social positioning with sexual roles.